Legal Protections For Consumer Against Advertisements From Artificial Intelligence - Andreas, Gertrud Felita Maheswari; P. Soemartono, R.M. Gatot (Universitas Muhammadiyah Sumatera Utara, 2025)
Artificial intelligence offers numerous benefits, but its misuse by businesses poses significant risks, particularly in creating misleading advertisements. For instance, companies may exploit AI to fabricate the likeness and voice of public figures in promotional videos, raising ethical and legal concerns. In Indonesia, the absence of specific legislation governing the commercial use of AI allows businesses to evade accountability and regulatory scrutiny. This gap in the legal framework prompts critical questions about liability: should responsibility rest with the business utilizing AI, or with the developers of the AI technology itself? There is an urgent need for clearer regulations that delineate the responsibilities of both parties in cases of AI misuse, ensuring consumer protection and accountability in advertising practices